2017
DOI: 10.22456/1982-8918.65002
|View full text |Cite
|
Sign up to set email alerts
|

Incidencia De Los Juegos Cooperativos en Las Relaciones Interpersonales

Abstract: Resumen: Este estudio tuvo como objetivo identificar los efectos de una unidad programática (UP) de juegos cooperativos, sobre díadas (aceptación y rechazo) y las características del grupo. Se siguió una metodología de investigación-acción; participaron 78 alumnos de 7 a 9 años (M = 8,3; DP = 0,33), 38 chicos (48,7%) y 40 chicas (51,3%). Al inicio y al final de la UP se aplicó un cuestionario sociométrico para identificar díadas reales de elección y de rechazo, y las dinámica grupales (Índice de Cohesión Grupa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 9 publications
(15 reference statements)
1
4
0
4
Order By: Relevance
“…The interviews illustrate that the Physical Education teachers interviewed feel the need to use collaborative activities when planning lessons through the CLIL approach. In this regard, the introduction of collaborative activities can also be useful to strengthen social dynamics within the group, enhancing prosocial behavior and empathy among students (Andueza and Lavega, 2017). In addition, this means that CLIL may entail a change in Physical Education methodology, making it more participative, inclusive and collaborative, which are ultimately some of the current trends in Physical Education because these features help to achieve a range of educationally beneficial objectives related to many different domains, such as the physical, lifestyle, affective, social and cognitive (Dyson et al, 2004;Kirk, 2010Kirk, , 2013.…”
Section: Discussion Of Qualitative and Quantitative Findingsmentioning
confidence: 99%
See 2 more Smart Citations
“…The interviews illustrate that the Physical Education teachers interviewed feel the need to use collaborative activities when planning lessons through the CLIL approach. In this regard, the introduction of collaborative activities can also be useful to strengthen social dynamics within the group, enhancing prosocial behavior and empathy among students (Andueza and Lavega, 2017). In addition, this means that CLIL may entail a change in Physical Education methodology, making it more participative, inclusive and collaborative, which are ultimately some of the current trends in Physical Education because these features help to achieve a range of educationally beneficial objectives related to many different domains, such as the physical, lifestyle, affective, social and cognitive (Dyson et al, 2004;Kirk, 2010Kirk, , 2013.…”
Section: Discussion Of Qualitative and Quantitative Findingsmentioning
confidence: 99%
“…In this regard, three of the questions show opposing trends when the mean scores of males and females are compared. This might be related to the differences by gender that are often found regarding both interpersonal relations, for example, focusing on acceptance within the group (Andueza and Lavega, 2017), and CLIL (Doiz et al, 2014;Fernandez-Barrionuevo and Baena-Extremera, 2018). Therefore, it is necessary to carry out further research on this topic, because the effects on sociometric measures might need longer to appear (van der Wilt et al, 2019).…”
Section: Discussion Of Qualitative and Quantitative Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…CIENCIAS HUMANAS Y SOCIALES -FORO "JOSÉ MARÍA CAGIGAL" | SOCIAL SCIENCES -"JOSÉ MARÍA CAGIGAL" FORUM Metodología cualitativa en el estudio del juego tradicional | Qualitative Methodology in the Study of Traditional Games Numerosas investigaciones realizadas constatan que cada uno de estos dominios originan consecuencias distintas sobre la conducta motriz de las personas participantes, ya sea sobre aspectos de relación interpersonal (Parlebas, 2012), de cohesión del grupo (Andueza & Lavega, 2017;Parlebas, 2010), de integración (Lavega, Planas, & Ruiz, 2014), o de conflictos (Collard & Oboeuf, 2007;Dugas, 2008;Sáez de Ocáriz & Lavega, 2015), como de transferencia de aprendizajes decisionales (Parlebas & Vives, 1969;Parlebas & Dugas, 1998), como también en la vivencia de emociones (Duran & Costes, 2018;Duran et al, 2014;Lavega, Alonso, Etxebeste, Lagardera, & March, 2014;Lavega, Sáez de Ocáriz, Lagardera, March, & Puig, 2017;Muñoz, Lavega, Serna, Sáez de Ocáriz, & March, 2017).…”
Section: Domains Of Motor Action and Emotionsunclassified
“…La investigación se ha realizado con miles de participantes, inicialmente con estudiantes universitarios de primer curso de diversas universidades de España, Portugal, Brasil y Suiza, en el marco de asignaturas prácticas que Numerous studies have shown that each of these domains leads to different consequences in the motor behavior of the participants, either on aspects of their interpersonal interactions (Parlebas, 2012), on group cohesion (Andueza & Lavega, 2017;Parlebas, 2010), on integration (Lavega, Planas & Ruiz, 2014) or on conflicts (Collard & Oboeuf, 2007;Dugas, 2008;Sáez de Ocáriz & Lavega, 2015), as well as on the transfer of decisional lessons (Parlebas & Vives, 1969;Parlebas & Dugas, 1998) and the experience of emotions (Duran & Costes, 2018;Duran et al, 2014;Lavega, Alonso, Etxebeste, Lagardera & March, 2014;Lavega, Sáez de Ocáriz, Lagardera, March & Puig, 2017;Muñoz, Lavega, Serna, Sáez de Ocáriz & March, 2017).…”
Section: Participantesmentioning
confidence: 99%